A Rancang Bangun Prototype Fermentor dengan Dua Aerator untuk Mengembangbiakkan Ragi Saccharomyces Cerevisiae : A Prototype Fermentor Design with Two Aerators to Cultivate Saccharomyces Cerevisiae Yeast Using Molasses as Raw Material - Alfitra, M Hanif; Wanjri, Adam; Youfa, Rita; Tri Jayanti, Regna; gusfiyesi, Gusfiyesi (UIR Press, 2025)
This study discusses the design and development of a prototype fermentor with two aerators to cultivate Saccharomyces cerevisiae yeast using molasses as raw material. The fermentor was designed with a capacity of six liters, equipped with a pitched blade turbine mixing system and two aerators to increase oxygen supply during aerobic fermentation. The observed variables included fermentation time, pH, temperature, and brix level. The results showed that the highest yeast growth was achieved at 72 hours of fermentation with a cell count of 1.51×108 cells/ml. The use of two aerators proved to provide more uniform oxygen distribution compared to one aerator, thereby increasing yeast growth efficiency. Thus, the designed fermentor can be used as a learning model and further laboratory research in renewable energy bioprocess techhnology.